Customers Attitude towards E-commerce in Bangladesh: An Empirical Study on Some Selected B2C E-commerce Sites (Journal of Business and Technology (Dhaka), 2016)
This study aims at identifying salient attributes of e-commerce sites in Bangladesh. The study tries to assess the perception of customers about the performance of major-e-commerce sites on those attributes. Eighteen potential attributes are preliminarily selected, and after conducting a pre-test on 50 sample respondents eleven salient attributes are selected for the study. Finally 108 respondents are taken as the study sample. Mertin Fishbeins multi-attribute attitude models adopted to measure the customers attitude. Respondents were asked their belief and evaluation towards some B2C ecommerce sites. The benchmark of positive belief is hypothesized as 4 in a 5 point scale. The significance of the difference between observed mean of customers belief and the predetermined benchmark is measured by left tailed Z statistic. It is found that the sample respondents believe that the performance of the B2C e-commerce sites in Bangladesh is up to the benchmark in teams of only two attributes among the eleven. The findings of this study may be used by the existing B2C e-commerce companies as well as by the future e-commerce entrepreneurs in Bangladesh to establish a quality and customer-driven B2C e-commerce industry. Even the customers will be benefitting if the industry considers the findings of the study.Journal of Business and Technology (Dhaka) Vol.10(1) 2015; 37-54